The European 'Other' in Poland's Conservative Identity Project. Issue 1 (2nd January 2017) - O'Neal, Molly
Abstract: Since taking office in November 2015, Poland's conservative government has pressed for a sweeping reinterpretation of the past, and a re-envisioning of the future, of the political community. This conservative identity project idealises the allegedly fully sovereign Poland of the interwar period and repudiates the normative commitments underpinning Poland's accession to the European Union. The worldview of the conservative government's liberal critics, by contrast, represents a fusion of the inclusive nationalism asserted in opposition to communist rule with the affirmation of a European identity. The reawakening of historically resonant debates about the nature of Poland's European-ness, emphasizing the centrality of the (Western) European 'other' in Poland's national idea, carries significant implications for its relations within the international environment.